Exome sequencing contributes to identify comorbidities in a rare case of infant ARDS induced by the CD40LG mutation - Xue Gong; Yunru He; Guoyan Lu; Yulin Zhang; Yu Qiu; Lina Qiao; Yifei Li (BMC, 2022)
Abstract Background Acute respiratory distress syndrome (ARDS) causes significant mortality in young children with certain diseases. Early diagnosis and treatment can reduce infant mortality. Here, we report a rare case of exome sequencing in the early diagnosis of immunodeficiency in an infant. Case presentation A four-month-old full-term male infant presented with severe shortness of breath, hypoxemia, and unexplained parenchymal lung lesions. A series of examinations were performed to search for potential culprit viruses but negative results were obtained with the only exception being the rhinovirus that tested positive. The child's family history revealed he had a brother who died of severe infection at the age of two years. We performed an exome sequencing analysis and a mutation analysis of CD40LG to obtain genetic data on the patient. Besides, we used flow cytometry to measure the CD40LG expression levels of activated T cells. A retrospective review of all the CD40LG mutant-induced X-linked hyper IgM syndromes (XHIGM) had been conducted to assess the differences between clinical and genetic molecular features. Finally, a regular intravenous immunoglobulin (IVIG) regimen led to steady breathing, the correction of hypoxemia, and a progressive improvement of lung CT scans. During follow-up, the patient received an IVIG regimen and his CT images improved. Moreover, his parents took advantage of pre-implantation genetic testing with in vitro fertilization to have a healthy twin offspring who did not carry such a mutation according to the early exome sequencing for the proband. Compared with other CD40LG mutant cases in our center, this proband displayed a normal plasma immunoglobulin level and he should be the youngest infant to have a molecular diagnosis of XHIGM. Conclusion Usually, XHIGM would not be suspected with a normal plasma immunoglobulin concentration. However, as we could not identify a potential comorbidity or risk factor, exome sequencing helps target this patient's real facts. Thus, this case report calls for exome sequencing to be performed in the case of unexplained infections when immunodeficiency is suspected after general immunological tests, especially for cases with a contributive family history among infants as the maternal transfused immunoglobulin might mask immune deficiency.